2023
DOI: 10.3389/fgene.2022.1041383
|View full text |Cite
|
Sign up to set email alerts
|

siMS score- method for quantification of metabolic syndrome, confirms co-founding factors of metabolic syndrome

Abstract: Background: Adipose tissue is a dynamic endocrine organ, a highly active metabolic tissue, and an important source of cytokines. Inflammatory factors play an important role in visceral obesity associated with insulin resistance (IR), metabolic syndrome (MS), hypertension, non-alcoholic fatty liver disease (NAFLD), diabetes mellitus type 2 (DM2), endothelial dysfunction (ED) and atherosclerosis.Objectives: To examine corelation of siMS score, as a quantification method for metabolic syndrome (MS), with insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The findings demonstrated that siMS score, CMI and metSSS are all associated with increased risk of MCI and lower MMSE score. These scores have been proven optimal methods for quantification of MetS, and the severity [ 21 23 ]. Previous studies reported that they were associated with increased risk of stroke, cardiovascular diseases, all-cause mortality [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings demonstrated that siMS score, CMI and metSSS are all associated with increased risk of MCI and lower MMSE score. These scores have been proven optimal methods for quantification of MetS, and the severity [ 21 23 ]. Previous studies reported that they were associated with increased risk of stroke, cardiovascular diseases, all-cause mortality [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that MetS is a risk factor for cognitive impairment among general population [ 16 ], no matter young [ 17 ], middle-aged [ 18 ] or elderly individuals [ 19 , 20 ]. In addition, several novel metabolic indices, such as metabolic syndrome (siMS) score [ 21 ], cardiometabolic index (CMI) [ 22 ] and metabolic syndrome severity score (MetSSS) [ 23 ], have been demonstrated to be promising indicators for predicting and quantifying MetS and its severity, with relatively high sensitivity and specificity. However, these associations between these indices and MCI are yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the case of the IDF, this result is consistent with a recent work that examined the correlation of the siMS score, a quantification method for metabolic syndrome, with insulin resistance and other cofounding factors of metabolic syndrome in 451 obese patients with pre-metabolic syndrome and metabolic syndrome. In this research, the IDF classification was applied to diagnose metabolic syndrome, and it was found that males had a higher prevalence of MetS versus females (24) .…”
Section: Factors Associated With Metsmentioning
confidence: 99%
“…MetS comprises a cluster of "cardiometabolic risk" factors, including high blood sugar, hypertension, hypertriglyceridemia, low high-density lipoprotein cholesterol, and abdominal obesity. Pre-MetS denotes a set of clinical and biochemical features manifesting metabolic irregularities in specific aspects, albeit not fully meeting the diagnostic criteria for MetS (1)(2)(3)(4). The combined impact of these components and ongoing metabolic disruptions significantly increase the risk of cardiovascular disease (CVD) (3) and cancer (4).…”
Section: Introductionmentioning
confidence: 99%